PENGEMBANGAN BAHAN AJAR PUISI BERBASIS MODEL PICTURE AND PICTURE PADA SISWA KELAS VIII SMP AL-RAZI SINAR HARAPAN TAHUN PEMBELAJARAN 2022-2023 - Nurapriana Nurapriana (LP2M Universitas Muslim Nusantara Al Washliyah, 2023)
The background of this research is the lack of literature teaching materials in poetry learning activities in class VIII SMP Al-Razi Sinar Harapan, so it is necessary to develop products in the form of picture and picture-based poetry teaching materials as media/tools used in the learning process. One effort that can be done is to develop teaching materials that can support students' knowledge, so that teaching materials are designed in such a way that students can carry out activities while learning in class. The purpose of this study was to determine the development of picture and picture model-based poetry teaching materials in class VIII SMP Al-Razi Sinar Harapan, to find out the feasibility of picture and picture model-based poetry teaching materials in class VIII SMP Al-Razi Sinar Harapan, and to find out the response from educators and students regarding poetry teaching materials products based on picture and picture models in class VIII SMP Al-Razi Sinar Harapan. The research method used in this research is the Research & Development method. The subject of research on product development in this study is the validator. The research was carried out by filling out the validation sheet provided, the validator in this study was the subject teacher. In addition, the subjects of this study were students of class VIII SMP Al-Razi Sinar Harapan. The object of this research is poetry teaching materials based on picture and picture models for class VIII students of SMP Al-Razi Sinar Harapan, located in Medan Johor sub-district, Medan City district. Based on the research results, the ability to write poetry obtained by students before the development of teaching materials was carried out, namely 63.55, which before the process of developing teaching materials was in the sufficient category. Furthermore, after developing poetry teaching materials based on the picture and picture model, it showed that the average score for students' ability to write poetry was 71.75 and then increased to good after the process of developing poetry teaching materials based on the picture and picture model for class students VIII SMP Al-Razi Sinar Harapan. Thus, the results of this study indicate that the design of developing poetry teaching materials based on the picture and picture model for class VIII students of SMP Al-Razi Sinar Harapan is declared successful and good. Keywords: Development, Teaching Materials, Picture and Picture Models